ANALISIS PERBEDAAN KINERJA DAN RISIKO REKSADANA SAHAM, REKSADANA PENDAPATAN TETAP, IHSG DAN INDEKS OBLIGASI DENGAN METODE SHARPE - Hapsari, Dhevita Niken; Hardiningsih, Pancawati (Jurnal Ilmiah Telaah Manajemen, 2005)
The aim of this research is examining the differences among Reksadana Stock Rate Return, Reksadana Fixed Income, Share Merger Price Index, and Obligation. Beside it also examines the availability of sharpe as the mean proxy of Reksadana Performance with the Free risk Rate Return which is valued by Indonesian Bank Certificate.This research uses 11 samples Reksadana Stock and Fixed Income Reksadana which is in the form of collective Investment Contract that has got an effective license from BAPEPAM (Capital Investment Controller Board) since July, 1996 and still exists during research period (2000-2004) and its unit has been traded in the society in Indonesia. The hyphothesis uses Mann Whitney shows that : (1) Reksadana stock Rate Return and Rate of Share Merger Price Index do not have significant differences (sig = 0,096). (2) There are no significant differences between the Fixed Income of Reksadana Return and Obligation Return (sig = 0,743). (3) There are significant differences between The Risk of Reksadana Stock and Share Merger Price Index’s risk (sig = 0,000). (4) The risk of Fixed Income Reksadana and Obligation’s Risk have significant difference (sig = 0,000). (5) Reksadana Performance Stock, The Fixed Income Reksadana, Share Merger Price Index and Obligation show that they do not have a significant differences (sig = 0,949).